Unique Terracotta Figurine from Singoor, District Chitral, Pakistan: Contextualizing Possible Hariti Figurine in the Buddhist Wilderness? - Zahir, Muhammad (Ancient Pakistan, 2016)
The archaeology and history of District Chitral in Khyber Pakhtunkhwa Province, Pakistan, is not very well understood in terms of major historical events and the character of its relationships with surrounding regions in South Asia and beyond. In fact, systematic archaeological research has recently started in Chitral, which suggests close linkages between Chitral and north-western Pakistan, particularly within the context of protohistoric cemeteries. Though Buddhism was a major phenomenon during the 1st millennium CE in most of north-western Pakistan and adjoining areas of Central Asia, Trans-Pamir region and China, there are very scarce evidence of Buddhism in Chitral, leading to suggestion of Chitral as being a ‘backwater’ of Buddhism in South Asia. The finding of a unique terracotta female figurine from Singoor village, Chitral, throws light on this interesting period of Chitral history and its relationships with Gandharan Buddhism. The present paper investigates the Singoor terracotta figurine and contextualizes it within the wider geographical, archaeological and historical contexts of Chitral and the surrounding region. The chaîne opératoire of the construction technology of the terracotta figurine revealed complex construction processes and choices made during the construction of the figurine and its linkage with possible religious ideologies. The paper suggests that the construction and style of the figurine is linked with the terracotta figurines from protohistoric cemeteries and early historic terracotta figurines from the Vale of Peshawar or Gandhara. Furthermore, the paper argues that the Singoor figurine is a representation of the Buddhist deity Hariti and that it is probably linked with the cult of Hariti in Gandhara during the first half of the 1st millennium CE.